1) (2m/2m+n - 4m²/4m²+4mn+n²)/(2m/4m²-n² + 1/n-2m) = - 2m(2m-n)/2m+n
1) 2m/2m+n - 4m²/(2m+n)² = 4m²+2mn-4m²/(2m+n)² = 2mn/(2m+n)²
2) 2m/4m²-n² + 1/n-2m = 2m/(2m-n)(2m+n) + 1/(n-2m) = 2m-2m-n/(2m-n)(2m+n) = - n/(2m-n)(2m+n)
3) - 2mn*(2m-n)(2m+n)/(2m+n)²*n = - 2m(2m-n)/2m+n
2) (x²/x+y - x³/x²+y²+2xy)/(x/x+y + x²/y²-x²) = x(y-x)/x+y
1) x²/x+y - x³/x²+y²+2xy = x²/x+y - x³/(x+y)² = x³+x²y-x³/(x+y)² = x²y/(x+y)²
2) x/x+y + x²/y²-x² = x/x+y + x²/(y-x)(y+x) = xy-x²+x²/(y-x)(y+x) = xy/(y-x)(y+x)
3) x²y * (y-x)(y+x)/(x+y)² * xy = x(y-x)/x+y